IL-17F gene polymorphism is associated with susceptibility to acute myeloid leukemia - Wróbel, Tomasz (Springer Berlin Heidelberg, 2014)
PURPOSE: Recent studies have suggested that Th17 cells may play a role in the pathogenesis of acute myeloid leukemia (AML). This subset of CD4+ cells is characterized by interleukin (IL)-17A and IL-17F production, which share strong homology, and surface expression of the IL-23 receptor (IL-23R). The present study aimed to determine the association between the polymorphic features located within the IL-17A, IL-17F and IL-23R genes and disease susceptibility, progression and response to therapy. In addition, the relationship between the polymorphic variants and the plasma IL-17 levels in patients was analyzed. METHODS: For this purpose, 187 individuals of Polish origin including 62 AML patients and 125 healthy controls were typed for IL-17A (rs2275913; G-197A), IL-17F (rs763780; A7488G; His161Arg) and IL-23R (rs11209026, G1142A; Arg381Gln) alleles. RESULTS: The rs763780 IL-17F polymorphism appeared to be associated with susceptibility to the disease. The presence of the minor (G) variant (RR = 4.76, p < 0.001) and its homozygosity (RR = 23.02, p < 0.005) was more frequent among patients than healthy individuals. No significant association was observed for either other polymorphisms studied or IL-17 levels. CONCLUSIONS: Thus, the rs763780 IL-17F polymorphism was found to be associated with predisposition to AML in the Polish population.